ASSESSMENT OF ABYADH SYAFAQ AT THE EARLY TIME OF ISHA ASTROPHOTOGRAPHY METHOD: PENGKAJIAN SYAFAQ ABYADH PADA AWAL WAKTU ISYA METODE ASTROFOTOGRAFI - Nurqolbi, Yusuf; Noosy, Aminuddin (ELFALAKY: Jurnal Ilmu Falak, 2024)
Studying observations to determine the start of Isha using astrophotography techniques is an interesting area of ​​research. This method is gaining popularity among astronomers and institutions for capturing images of the crescent Moon and the night sky. The main objective of this research is to analyze Syafaq Abyadh observations in different sky brightness zones and assess the accuracy of using astrophotography techniques to determine the start of the Isha prayer time. This research uses a qualitative descriptive approach, namely collecting primary data from the field and complementing it with information from relevant literature and scientific sources. This research produced two findings. First, several factors were discovered, including; light pollution, weather, even clouds and rain which affect the rapid loss of Syafaq light in areas with different levels of sky brightness. Second, of the three locations tested, the perfect location that is most suitable for using Syafaq observations using the astrophotography method to determine the start of Isha time with a sun height of -18º is Empurancak Jepara beach (sky brightness is green and below/class 4 and below).